Swansong: Can Hope Survive an Indeterminate Prison Sentence?. (25th July 2019) - Orrell, Katya
Abstract : Chekhov's play Swansong could be describing a prison wing. Depicting a drunk, elderly comic actor who has fallen asleep after the performance is over and awaking to a deserted theatre, he speaks, and is answered by the prompter responding from the darkness, an image not unlike the therapeutic dyad. Over recent years, working psychodynamically in a man's prison has felt dangerous. For someone serving an imprisonment for public protection (IPP) sentence, a sentence with no finite ending, the threat of psychic death, of hope, is the sword of Damocles which hangs over his every day. I examine what it means to undertake clinical work with a man who never knows when he will leave prison. Using the concept of the swansong, a song considered to be more beautiful because of the fragility of a life that is about to end, I ask what is happening when a prisoner whose unprocessed grief and rage threatens to destroy all creativity. I explore how the danger of his internal destructiveness meets and is reflected by the actual threat of our extinction as forensic psychotherapists. What happens to the ability to contain, when the relationship with the prison itself feels dangerous, when each session feels like our swansong?